Migration and Diasporic Identity in Scholastique Mukasonga’s Un si beau diplôme ! - Marda Messay (Studies in 20th & 21st Century Literature, 2025)
In Un si beau diplôme! (2018), Franco-Rwandan author Scholastique Mukasonga recounts her experiences as a refugee in Burundi and her quest to obtain a degree in social work. She also describes the challenges she had to overcome to get her foreign degree recognized and to be able to practice her chosen profession when she and her family immigrated to Djibouti in 1986, and then to France in 1992. Mukasonga concludes her text by narrating a recent visit to an economically and socially transformed Rwanda. As a whole, the text underscores the importance of her degree, which was ultimately essential to her survival. However, this essay focuses on how Mukasonga navigates each of these physical displacements. For instance, she was able to navigate the gender-specific perils of exile as a female refugee in Burundi by developing her professional identity of social worker, by refusing to be immobilized by her refugee status, and with the support of other female refugees. I also study her experiences of inclusion and racial exclusion in Djibouti and France and how she developed a more expansive and inclusive sense of identity, that of an African and French woman. Finally, I examine how Mukasonga’s return to a changed Rwanda allowed her to reconnect and altered her perspective on her homeland. This essay argues that Mukasonga’s experiences expand our understanding of migration by not only engaging with issues of gender, hegemony, belonging, agency, otherness, solidarity, and diasporic identity, but also by counteracting and transcending dominant discourses and expectations of migratory experiences.
Keywords: Scholastique Mukasonga; migration; Rwanda; diasporic identity